Spatial distribution of Malaria in peninsular Malaysia from 2000 to 2009 - Alias, H.; Surin, Johari; Mahmud, R.; Mokhtar, A.S. (BMC, 2014)

(untitled)
Malaria is still an endemic disease of public health importance in Malaysia. Population at risk of contracting malaria includes indigenous people, traditional villagers, mobile ethnic group and land scheme settlers, immigrants from malaria endemic countries as well as jungle workers and loggers. The predominant species are Plasmodium falciparum and P.vivax. Increasing number of P.knowlesi infections is also encountered. The principal vectors in Peninsular Malaysia are Anopheles maculatus and An cracens. This study aims to determine the changes in spatial distribution of malaria in Peninsular Malaysia from year 2000-2009.